2021
DOI: 10.3390/s21124212
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Continuous Authentication Based on Touch Dynamics Biometrics for Mobile Banking Applications

Abstract: As smart devices have become commonly used to access internet banking applications, these devices constitute appealing targets for fraudsters. Impersonation attacks are an essential concern for internet banking providers. Therefore, user authentication countermeasures based on biometrics, whether physiological or behavioral, have been developed, including those based on touch dynamics biometrics. These measures take into account the unique behavior of a person when interacting with touchscreen devices, thus hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The motivation behind this exploration is to investigate and foster comprehension of basic worries blunder-free, disappointment-free, more usable and best executable mmedical applications because the patient can't afford any misconception due to horridness [19]. This Idea will be founded on quantitative request.…”
Section: Methodsmentioning
confidence: 99%
“…The motivation behind this exploration is to investigate and foster comprehension of basic worries blunder-free, disappointment-free, more usable and best executable mmedical applications because the patient can't afford any misconception due to horridness [19]. This Idea will be founded on quantitative request.…”
Section: Methodsmentioning
confidence: 99%
“…Several performance indicators have shown that deep neural networks can provide the high accuracy required for verifying human identity. Estrela et al [9] presented a behavioral measure of biometrics for user verification in banking applications to prevent fraud and impersonation attacks. It achieved accuracies of 90.68% and 97.05% when using biometrics for banking authorization in various scenarios.…”
Section: Background and Related Workmentioning
confidence: 99%
“…In authentication problems, NB determines the probability that a user is genuine, given the known probabilities extracted from training data in the model. Estrela et al [ 54 ] proposed a framework using touch dynamics biometrics for continuous authentication in mobile banking applications. Touch dynamic is a biological recognition method based on individuals’ touch patterns.…”
Section: Machine Learning Models In Authentication Schemes Of Telehealthmentioning
confidence: 99%